Volumetric lung nodule segmentation in thoracic CT scan using freehand sketch. Issue 14 (14th October 2020) - Pramod Kumar, S.; Latte, Mrityunjaya V.; Siri, Sangeeta K.
Abstract : The authors presented a novel computerised scheme to segment pulmonary nodules using freehand sketch. Here, freehand sketching is considered to identify the location of a nodule and it serves as a natural way and also it provides inferring adaptive information i.e. size, density, texture and mass centre etc. The proposed scheme includes two phases. In first phase using the freehand sketch analysis the multi seed points to select RoI. In the second phase nodule volumetric extraction is done using geometric modelling and implicit surface reconstruction for volumetric analysis. Spherical bins are used for ray triangle intersections and then local implicit surface fitting and blending method for surface reconstruction and depiction. The performance of the proposed scheme is assessed by accuracy and consistency using 112 CT examinations from LIDC. The IoU and ASD were used to assess the discrepancy between proposed method and inter observer agreement in the proposed approach. In estimating the reproducibility, the discrepancy in proposed scheme and the manual contouring by the expert is observed to be on an average of 0.13 ± 0.07 mm and 3.04 ± 1.7 mm respectively. The experiment shows that, the proposed scheme performs reasonably well and demonstrate merit of freehand sketch.